2017
DOI: 10.4172/2165-784x.1000268
|View full text |Cite
|
Sign up to set email alerts
|

A K-Nearest Neighbor Model of Light-Duty Vehicle Emission Factors Considering Pavement Roughness

Abstract: Emission factors are very important measures for developing an emission inventory, making decisions, designing control strategies, mitigating climate change, and even improving public health, in terms of respiratory system diseases. The emission factors could be either measured from field tests or estimated by an emission model. Existing models seldom consider the impacts of some special factors such as pavement roughness. As the impacts of the pavement roughness on emissions are very complicated, a linear mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Li et al and Jiao built evaluation models to estimate vehicle emission factors with data concerning pavement conditions and found that the relationship between roadway pavement conditions and vehicle emissions was non-linear [ 15 , 16 ]. Peters et al explored approaches as to how to coordinate traffic signals to reduce congestion and carbon dioxide emissions [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al and Jiao built evaluation models to estimate vehicle emission factors with data concerning pavement conditions and found that the relationship between roadway pavement conditions and vehicle emissions was non-linear [ 15 , 16 ]. Peters et al explored approaches as to how to coordinate traffic signals to reduce congestion and carbon dioxide emissions [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, based on the on-road measured emission data on one dedicated light duty vehicle from the PEMS and the related pavement roughness information with a sampling interval of 5 m along more than 1,000 miles road tests in Texas, USA, Li et al [19] developed several nonlinear models such as the K-nearest neighbors (K-NN) and Neural Network models, for four major exhaust emission indexes (CO 2 , CO, HC and NO x .) The estimated emissions from those identified models are highly correlated to the real measured values.…”
Section: Recent Studies On Pavement Roughness and Vehicle Emissionsmentioning
confidence: 99%
“…It seems that shortening the idling duration is determinative for the CO 2 emission reduction. However, a number of emission study results demonstrated that the CO 2 emission is highly associated with vehicles' operations [20,21].…”
Section: Introductionmentioning
confidence: 99%